Estimation of P-multipliers for laterally loaded pile groups in clay and sand. (3rd April 2019) - Talebi, Amir; Derakhshani, Ali
ABSTRACT: Pile-supported marine structures are generally subjected to lateral loads caused by earthquakes, waves, currents, etc. p–y curves are traditionally used to evaluate the response of a pile under lateral loading. For a group of piles, p–y curves need to be modified using a factor referred to as P-multiplier. In this study, two new models were developed to predict the P-multiplier for the pile groups in clay and sand using genetic programming. To this end, an extensive database was gathered from the previous experimental studies on the pile groups. In addition to input parameters used for P-multiplier estimation in design guidelines, several other governing parameters were considered in this study. The accuracy of the proposed formulas was investigated by various error measures and it was shown that the new models outperform the previous approaches. Moreover, the uncertainties incorporated in the new formulas were assessed and also a sensitivity analysis was performed.